Active methodology in emergency remote teaching with nursing students: experience report (Research, Society and Development, 2022)
In the face of a COVID-19 pandemic, digital technologies were used as essential tools for the teaching-learning process in remote teaching, which have innovative and transformative potential for skills training resulting from the combination of active learning strategies and technologies. The present study aims to describe the experience of using teaching strategies of active methodology in Emergency Remote Teaching with nursing students at a federal university in the interior of Minas Gerais. The experience was developed by a nurse remotely, as a result of the fulfillment of practical discipline in formal teaching and learning in the doctoral course, in the context of the pandemic. Initially, classes were recommended by the supervisor, followed by contact with the teachers, planning and execution of the class. In teaching practice, the nurse assumed the role of mediator using teaching strategies of active methodology. The use of these in remote teaching made it possible to reduce distances, stimulate participation and dialogue with students who acted as protagonists, and the development of skills. For nurse, it represented an experience of meeting subjects, reinforcing the belief in transforming education, including enjoying the ludic with technological resources. As a limitation of the study, there is the difficulty in monitoring the results of the experience regarding the knowledge built and skills developed. We emphasize the need for more studies that investigate the active methodology of learning in the development of competences with nursing students.